KEPUASAN MAHASISWATERHADAP PROSES PERKULIAHAN DI FMIPA UNNES - Dewi, Novi Ratna; Asikin, Moh (Lembaran Ilmu Kependidikan, 2009)
The aim of this research is to know the student's degree of satisfaction towardlecture processes. The study was conducted in the odd semester at the Faculty ofMathematics and Science in 2008. The subjects of the research were students of ninemajors of four departments in the faculty. The research subjects, numbering 540students were selected proportionally depending on the number of students in eachmajor. The data of the students' satisfaction were collected with a questioner. Thestudy showed that 74% students felt satisfied with the lectures at the faculty. Threethings which need improvement are: written information of the lesson objective atthe beginning of every session, the compliance of number of hours in each meetingwith the existing regulations, and the return of students' corrected work.Kata kunci: kepuasan layanan, perkuliahan, dan kinerja mahasiswa